Praktik Pengungkapan Informasi Environmental, Social And Governance (ESG) Dalam Penerapan GCG - Sarnisa, Wandha Dani; Rafianamaghfurin, Rafianamaghfurin; Djasuli, Mohamad (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
Environmental, social and governance (ESG) issues resulting from company activities have recently become the focus of stakeholder assessment in assessing the company's sustainability performance. This is a driving factor for many companies to voluntarily disclose sustainable financial reporting regarding ESG information. This study aims to examine and describe the practice of disclosing Environmental, Social, Governance (ESG) information in the application of GCG in companies. This study used a qualitative research method with a literature review approach. Sources of research data are several articles and journals from previous research relating to Environmental, Social, Governance (ESG) disclosure practices and GCG implementation in companies. The results of the literature review research show that the existence of Environmental, Social, Governance (ESG) information disclosure practices will increase the value of company performance and improve the company's good reputation in the long term, thereby attracting investors' interest to invest, which has an impact on long-term sustainability company.